Loss of HIV candidate vaccine efficacy in male macaques by mucosal nanoparticle immunization rescued by V2-specific response - Mohammad Arif Rahman; Massimiliano Bissa; Hanna Scinto; Savannah E. Howe; Sarkis Sarkis; Zhong-Min Ma; Anna Gutowska; Xunqing Jiang; Christina C. Luo; Luca Schifanella; Ramona Moles; Isabela Silva de Castro; et al. (Nature Communications)
Abstract Systemic vaccination of macaques with V1-deleted (ΔV1) envelope immunogens reduce the risk of SIVmac251 acquisition by approximately 60%, with protective roles played by V2-specific ADCC and envelope-specific mucosal IL-17+NKp44+ innate lymphoid cells (ILCs). We investigated whether increased mucosal responses to V2 benefit vaccine efficacy by delivering oral nanoparticles (NPs) that release V2-scaffolded on Typhoid Toxin B (TTB) to the large intestine. Strikingly, mucosal immunization of male macaques abrogated vaccine efficacy with control TTB or empty NPs, but vaccine efficacy of up to 47.6% was preserved with V2-TTB NPs. The deleterious effects of NPs were linked to preferential recruitment of mucosal plasmacytoid dendritic cells (pDCs), reduction of protective mucosal NKp44+ ILCs, increased non-protective mucosal PMA/Ionomycin-induced IFN-γ+NKG2A-NKp44-ILCs, and increased levels of mucosal activated Ki67+CD4+ T cells, a potential target for virus infection. V2-TTB NP mucosal boosting rescued vaccine efficacy, likely via high avidity V2-specific antibodies mediating ADCC, and higher frequencies of mucosal NKp44+ ILCs and of ∆V1gp120 binding antibody-secreting B cells in the rectal mucosa. These findings emphasize the central role of systemic immunization and mucosal V2-specific antibodies in the protection afforded by ΔV1 envelope immunogens and encourage careful evaluation of vaccine delivery platforms to avoid inducing immune responses favorable to HIV transmission.